Development, characterization, and prolonged shelf life of functional yogurt enriched with nanoencapsulated yellow Capsicum Annuum extract using whey protein - Faizah Musaed Mohammad Al-subhi (Applied Food Research)
This research examined the formulation and characterization of functional yogurt fortified with nanoencapsulated Yellow Capsicum Annuum Extract (YCAE) by the cold gelation of whey protein isolate (WPI). YCAE, obtained at a yield of 3.09 %, demonstrated a total phenolic content of 42.95 mg GAE/g and significant antioxidant activity (39.97 mg TEAC/g). HPLC study revealed notable phenolic substances, such as quercetin (607.00 µg/g), gallic acid (527.26 µg/g), and catechin (20.04 µg/g). The various ratios (50, 100, and 150 mg) of YCAE nanoencapsulated with WPI produced stable nanoparticles with dimensions between 103.99 and 145.60 nm, a polydispersity index of 0.451–0.651, and zeta potentials ranging from −26.40 to −34.60 mV, attaining high encapsulation efficiencies of 84.26–95.62 %. 100 YCAE-WPINPs exhibit notable tiny particle sizes, steady zeta potential, and elevated encapsulation efficiency. Yogurt compositions fortified with nanoencapsulated 100 mg YCAE exhibited increased protein content, especially in treatments T3 and T4. During a 21-day shelf life, these fortified yogurts, particularly T4, demonstrated enhanced stability, increased starter culture counts and total plate count (TPC), and maintained antioxidant activity. Sensory assessments indicated that T4, which includes encapsulated YCAE, obtained the greatest preference ratings for taste, texture, body, and overall acceptability. This study emphasizes the effective incorporation of nanoencapsulated bioactive components into yogurt, yielding a functional dairy product with enhanced nutritional and sensory qualities and facilitating creative progress in health-focused dairy product development.